2005
DOI: 10.1017/s0022215105005438
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic balloon dilatation of pharyngeal stricture under local anaesthetic

Abstract: Balloon dilatation is well established in the management of enteric strictures. The use of this technique in the pharynx has been reported under radiological and endoscopic guidance. We describe the hydrostatic dilatation of a benign pharyngeal stricture in a laryngectomy patient under local anaesthetic, without radiological guidance, in the ENT out-patient department. This procedure was effective and well tolerated in a patient who required regular dilatations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Indications and interventions for which transnasal esophagoscopy are used are displayed in Table . Overall, patients reported good tolerability of transnasal esophagoscopy while under topical anesthesia, and some studies even found better tolerability compared to transoral esophagoscopy under topical anesthesia or sedation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indications and interventions for which transnasal esophagoscopy are used are displayed in Table . Overall, patients reported good tolerability of transnasal esophagoscopy while under topical anesthesia, and some studies even found better tolerability compared to transoral esophagoscopy under topical anesthesia or sedation .…”
Section: Resultsmentioning
confidence: 99%
“…Another method is dilating over a guidewire or with mercury‐weighted dilators, which do not need a wire . Since the introduction of balloon dilatation in 1981, this procedure has become an alternative method of esophageal dilatation . Rees described her technique for balloon dilatation, with the patient under topical anesthesia, by inserting the endoscope and guidewire transnasally and positioning them so the transparent dilating balloon could be visualized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedural indications include biopsies of the laryngopharynx and esophagus, esophageal, neopharyngeal, and nasopharyngeal stricture balloon dilation,83–85 secondary tracheoesophageal puncture,86, 87 the delivery of flexible lasers, delivery of feeding tubes, injection of Botox into the esophagus,88 and the insertion of wireless pH monitoring devices 89…”
Section: Transnasal Esophagoscopymentioning
confidence: 99%